Composition of the essential oil of Hypericum salsolifolium Hand.-Mazz. and Hypericum retusum Aucher from Turkey - Bagci, Eyup; Yuce, Ebru (Soc Botanique France, 2011)
The composition of the essential oils of Hypericum salsolifolium Hand.-Mazz. and H. retusum Aucher was analyzed and 60 compounds were determined in total. GC and GC-MS analyses showed a-pinene (34.92%, 35.02% respectively) and limonene (12.38%, 12.34% respectively) as the most abundant components. No major differences were detected in the essential oil composition in both Hypericum species. The essential oil composition of them show some qualitative resemblances, on the contrary with the taxonomical classification based on morphological characters. The results are discussed in view of the distribution of the essential oil components in the Hypericum genus in means of chemotaxonomy and renewable resources.
Keywords: Hypericum salsolifolium; Hypericum retusum; essential oil; alpha-pinene; limonene